Herlyn-Werner-Wünderlich syndrome with late diagnosis: a propos of a case - Boria Alegre, Félix (2019)
Herlyn-Werner-Wünderlich syndrome is a rare congenital anomaly that affects the genitourinary system. It is defined by the triad of uterus didelphys, obstructed hemivagina, and ipsilateral renal agenesis. It consists in a Mullerian anomaly. Most patients remain asymptomatic until the menarche, when they present dysmenorrhea, pelvic pain, and a pelvic mass is noticed due to hematocolpos. We present the case of a 32-year-old patient studied for infertility. 3D transvaginal ultrasound and hysterosalpingography showed uterus didelphys and a blind hemivagina. Speculoscopy during menses revealed a normal cervix and a little orifice on the lateral vagina where blood could be seen draining from a fistulized hemivagina. The abdominal ultrasound showed ipsilateral renal agenesis, confirming the suspected diagnosis.